Study of compliance and impact of infant and young child feeding counseling in Patna district, Bihar - Singh, Alka; Ranjan, Amitabh; Thakur, A K (Indian Journal of Child Health, 2017)
Background: The infant and young child feeding (IYCF) practices have crucial role for physical and mental development of the child. Objective: To study the compliance to IYCF practices and impact of IYCF counseling in and around Patna district. Methods: Cross-sectional study was done in a hospital-based survey to find out compliance, and impact of IYCF practice counseling among infants and children attending a tertiary level hospital, Patna. Children in the age group, 6-24 months in and around Patna, were studied. Results: About 24% of the mothers initiated breastfeeding within an hour after birth. Exclusive breastfeeding for 6 months was practiced only by 36% of the mothers. Nearly, 43% of the mothers started complementary feeding at 6 months, and 45% of the infants were breastfed for 2 years. In the present study, 26% of mothers were using as age-appropriate complementary feeding and 35% of the mothers were feeding actively their child both during and after illness. Conclusion: Despite 3 years of counseling, compliance to IYCF practice in our area is low, and thus, the impact of IYCF counseling is poor in our area. Low knowledge score of mothers, lesser number of antenatal care visit is found to be an important factor responsible for low compliance.